Inside protonation of 1,8-diazabicyclo[6.6.n]alka-4,11-diynes - Balalaie, Saeed; Kunze, Andreas; Gleiter, Rolf; Rominger, Frank; Geis, Sibylle; Oeser, Thomas (European journal of organic chemistry, 2003)
Protonation of 1,8-diazabicyclo[6.6.3]heptadeca-4,11-diyne (4a), 1,8-diazabicyclo[6.6.4]octa-deca-4,11-diyne (4b), 1,8-diazabicyclo[6.6.5]nonadeca-4,11-diyne (4c), and 1,8-diazabicyclo[6.6.6]eicosa-4,11-diyne (4d) was achieved by treatment of 4a−4d with strong acids. Monoprotonation products were isolated in all cases, while for 4b and 4c diprotonation products were also obtained. X-ray investigations show inside protonation for the mono- and diprotonation products. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)